2014
DOI: 10.1007/s11136-014-0864-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural measurement equivalence of the EQ-5D-5L items for English-speaking Asians in Singapore

Abstract: The EQ-5D-5L items are likely to generate equivalent health outcomes between English-speaking Chinese and non-Chinese Singaporeans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…This indicates that, at least for the three data sets tested here, respondents appear to perceive the relative severity of the descriptive levels to be roughly the same across dimensions. This corresponds with previous studies in which general population respondents from several countries rated the descriptive levels using a numerical rating scale [19,20]. The improved performance associated with restricting the freedom of the 20-parameter model suggests that the number of parameters puts it at risk of overfitting to the observed data; modeling between-dimension variance in relative level distance did not improve predictions, suggesting that this is largely influenced by measurement error and random variance.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This indicates that, at least for the three data sets tested here, respondents appear to perceive the relative severity of the descriptive levels to be roughly the same across dimensions. This corresponds with previous studies in which general population respondents from several countries rated the descriptive levels using a numerical rating scale [19,20]. The improved performance associated with restricting the freedom of the 20-parameter model suggests that the number of parameters puts it at risk of overfitting to the observed data; modeling between-dimension variance in relative level distance did not improve predictions, suggesting that this is largely influenced by measurement error and random variance.…”
Section: Discussionsupporting
confidence: 86%
“…Through these studies, the final labels were selected from a larger initial pool of possible labels on the basis of several criteria, including approximate equidistance in severity rated by lay persons in a visual analogue scale task (medians close to 25th, 50th, and 75th percentile for level labels 2, 3, and 4), consistency in relative severity across dimensions, consistency in ranking, availability in colloquial language, and subjective reporting of how easy they were to understand [3]. Following the selection of labels, followup studies in English, Spanish, French, and Chinese indicate that the labels are perceived as describing relatively equal intervals across the five dimensions [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of respondents' failing to recognise the relative severity described by 'slight' and 'moderate' was reported in previous studies. 21,22 These issues suggest that interview-administration might be more appropriate when study samples comprise individuals with low literacy levels, such as old people.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Luo et al found that the interpretation and use of EQ-5D-5L response labels (e.g., ‘slight’, ‘moderate’, and ‘severe’) varied across Chinese, Malay, and English speakers in Singapore [23], whereas the English version gave similar outcomes in Chinese and non-Chinese English speakers in the same country [24], suggesting that there was no effect of culture on responses. Although a strict protocol is followed in producing other language versions of EQ-5D [25], it may not always be possible to find identical terms in all languages.…”
Section: Discussionmentioning
confidence: 99%